A combined numerical and experimental study on the forced convection of Al2O3-water nanofluid in a circular tube. (May 2018) - Ho, C.J.; Chang, C.Y.; Yan, Wei-Mon; Amani, Pouria
Highlights: Forced convection of nanofluid flowing through a circular tube is investigated. The cooling performance is examined in details. Heat transfer is significantly influenced by adding nano particles in coolant. Abstract: This research investigates the contribution of Al2 O3 nanoparticle suspensions on laminar forced convection heat transportation of Al2 O3 -water nanofluid flowing through a circular tube. In this regard, initially, the variation of the wall and bulk fluid temperatures and the values of local Nusselt numbers are experimentally evaluated along the tube. Next, numerically, the effect of various inlet temperatures from 25 to 50 °C on the important characteristics of the problem under study including pressure drop, Nusselt number and entropy generation are further examined through the constant property and temperature-dependent property modeling. The flow rate of the working fluid was ranged from 24 to 180 cm 3 /min corresponding Re = 120–2000. The imposed heat flux was 5.51 × 10 2 –1.23 × 10 4 W/m 2 . It is found that the addition of nanoparticles leads to the reduction of wall temperature and the enhancement of the Nusselt number, while it also causes an increase in the pressure drop along the tube. The results further reveal that the variable-property simulation provides more accurate predictions. The predicted pressure drop is decreased, and the predicted Nusselt number is increased by considering the temperature dependency of thermophysical properties of the nanofluid.